Impact of human-robot interaction on user satisfaction with humanoid-based healthcare - Kwon, Ohbyung; Kim, Jeonghun; Jin, Yoonsun; Lee, Namyeon (International Journal of Engineering and Technology, 2018)
Background/Objectives: The advent of self-service technology (SST) (e.g.,kiosks and Automatic Response System), has made it possible for service providersto make use of non-face-to-face channels to meet usersâ€™needs and decrease usersâ€™costs and time. On the other hand, however, more complex technology and/or services inhibit usersâ€™ satisfaction and,consequently,the intention to adopt SST, because such SST can instill fear in users. Nevertheless, at present, patients and other people who are interested in their own health and well-being are paying great attention to healthcare robots (as a form of SST)and,consequently, it has become crucial to investigate how these healthcare robots can positively influence usersâ€™ satisfaction with them. Hence, this study aims to empirically investigate the factors that affect usersâ€™ satisfaction with healthcare robots, especially in regard to human-robot interaction (HRI).Methods/Statistical analysis: We focused on the theory of heterophily and applied a series of factors identified in previous robot-adoption studies.Uniquely, this study focuses on usersâ€™ heterophily with healthcare robots, examining heterophily through three fundamental elements, empathy, professionalism, and personality, which we considered to be suitable fordetermining user satisfaction with HRI-based communication.To prove the validity of our hypotheses, we conducted an empirical testthat involved participants receiving a short health assessment from a robot.Findings: The findings of our empirical test supported our hypothesis that the lower the difference in empathy between a user and robot, the higher the level of user satisfaction with the humanoid-style healthcare service. Further, our results also suggest that heterogeneity between a user and healthcare robot is positively associated with user satisfaction.Improvements/Applications: First, to increase user satisfaction,robots must be provided with the ability to somehow recognizea userâ€™s personality and adjust their own accordingly before beginning the robot-based healthcare service. Secondly, usersâ€™ behavior patterns should be analyzed by the healthcare robot. Overall, our study empirically shows the importance of ensuring thatprofessionalism is present in healthcare-domain-related HRI.Â Â